1983
DOI: 10.1093/schbul/9.4.571
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Minor Physical Anomalies in Adult Male Schizophrenics

Abstract: The Waldrop anomaly score was used to assess the incidence of minor physical anomalies among 40 adult male Caucasian schizophrenics. This sample had a higher group mean anomaly score than that reported for the normal population (p less than .001). Those with higher anomaly scores evidenced poorer premorbid adjustment (p less than .05). A significant relationship also existed between anomaly scores and the subset of premorbid adjustment, Wechsler Adult Intelligence Scale Vocabulary scores, and the Neurological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(77 citation statements)
references
References 44 publications
4
73
0
Order By: Relevance
“…Recent studies have started providing additional information regardmental retardation were also prevalent. This study extends previous studies that have reported an neurological disorders is known to arise from the expansion of trinucleotide repeats between generations increased prevalence of certain minor physical abnormalities in schizophrenic patients [22][23][24][25] and suggests of affected individuals. 150 The evidence for dominant inheritance and anticipation, the apparent prevalence that other microdeletions (among other potential etiologies) may be causing the dysmorphic features of dominant genes in schizophrenia as well as the high frequency of human brain genes containing trinucleoidentified.…”
Section: Genetic Approachessupporting
confidence: 89%
“…Recent studies have started providing additional information regardmental retardation were also prevalent. This study extends previous studies that have reported an neurological disorders is known to arise from the expansion of trinucleotide repeats between generations increased prevalence of certain minor physical abnormalities in schizophrenic patients [22][23][24][25] and suggests of affected individuals. 150 The evidence for dominant inheritance and anticipation, the apparent prevalence that other microdeletions (among other potential etiologies) may be causing the dysmorphic features of dominant genes in schizophrenia as well as the high frequency of human brain genes containing trinucleoidentified.…”
Section: Genetic Approachessupporting
confidence: 89%
“…1 Minor physical malformations such as craniofacial asymmetries or dermatoglyphic irregularities are also increased in patients with schizophrenia suggesting an association with aberrant morphogenesis. 5,6 These physical abnormalities occurring outside the brain are considered nonspecific indicators of schizophrenia and are not thought to be involved in disease causation; however, from the perspective of a viral etiology this apparently reasonable assumption cannot be taken for granted because subtle defects in peripheral development could include immune tissues (eg, tonsillar lymphatics, thymus) and thus alter viral susceptibility or immune responses.…”
Section: Human and Epidemiological Studiesmentioning
confidence: 99%
“…Several neurological disorders like epilepsy, mental retardation and learning disabilities are associated with the presence of these anomalies. Studies comparing schizophrenic patients with normal controls also found an excess of MPAs in schizophrenics (15,16). In a study correlating MPAs with Wechsler Scale performance a strong correlation of MPAs with lower verbal IQ and poor premorbid adjustment was observed (16).…”
Section: Minor Physical Anomaliesmentioning
confidence: 97%
“…MPA found in the cephalic area, hands, and feet can indicate a neurodevelopmental problem dating back to the first gestational quarter. DM consists of digital and palmar line alterations and indicates second-trimester developmental problems (13)(14)(15)(16)(17).…”
Section: Chronological Markersmentioning
confidence: 99%